2013
DOI: 10.1111/jog.12099
|View full text |Cite
|
Sign up to set email alerts
|

Facility‐based review of 296 maternal deaths at a tertiary centre in India: Could they be prevented?

Abstract: More maternal deaths occurred in the medical than in the obstetrics wards at the facility. The leading causes were hepatitis, hemorrhage and puerperal sepsis. Most of the deaths were non-preventable as the women were critically sick at admission; however, substandard care and health service deficiency were contributory in some of the cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…The proportions are higher compare to previous some studies 7,11,18,20 , but represents a speciifc group dealt at peripheral secondary level or EmONC facilities of Bangladesh. The findings deserve attention for immediate actions by enhancing capacity at secondary level facilities of Bangladesh in managing obstetric complications with a focus to haemorrhage and eclampsia.…”
Section: Fig-3: Delay In Decision Making and Transfer To Referral Famentioning
confidence: 76%
See 2 more Smart Citations
“…The proportions are higher compare to previous some studies 7,11,18,20 , but represents a speciifc group dealt at peripheral secondary level or EmONC facilities of Bangladesh. The findings deserve attention for immediate actions by enhancing capacity at secondary level facilities of Bangladesh in managing obstetric complications with a focus to haemorrhage and eclampsia.…”
Section: Fig-3: Delay In Decision Making and Transfer To Referral Famentioning
confidence: 76%
“…The facility death review helped implementing remedial actions based on audit data and improved quality of care at facilities 8,11,17,27 . The death review process successfully identified medical causes and health system gaps.…”
Section: Fig-3: Delay In Decision Making and Transfer To Referral Famentioning
confidence: 99%
See 1 more Smart Citation
“…Missed diagnosis leads to tubal rupture, hemoperitoneum and hemorrhagic shock. It is an important cause of maternal mortality in the first trimester of pregnancy in Western as well as in Asian countries . Twin ectopic pregnancy is a rare occurrence with an estimated incidence of 1 in 20 000 spontaneous pregnancies .…”
Section: Introductionmentioning
confidence: 99%
“…It is an important cause of maternal mortality in the first trimester of pregnancy in Western as well as in Asian countries. 1 Twin ectopic pregnancy is a rare occurrence with an estimated incidence of 1 in 20 000 spontaneous pregnancies. 2 We describe one such case and discuss an interesting observation that has implications for the management of this rare type of ectopic pregnancy.…”
Section: Introductionmentioning
confidence: 99%